Мистецтво як універсальна форма відображення людського буття - Манько, К. Є. (ХНУРЕ, 2021)
The articles analyze art as a universal formula for reflecting human existence, highlighted by the specifics of art of different historical epochs. It has been found that art is a manifestation of the spiritual being of man, from time immemorial it reveals the spiritual essence of man, thus compensating for the incomplete human being.
Keywords: філософія; мистецтво